Influences of tourist motivation on CBT marketing strategies: case study of Kilim Geopark, Langkawi - Mohammad Afandi, Syamsul Herman; Ramachandran, Sridar; Shuib, Ahmad; Zameli, Nurul Hikmah; Matthew, Nitanan Koshy; Sapari, Mohamad Safee (2012)
Community based tourism (CBT) has been a well-known practices in many country. CBT provide tourists the opportunity to experience and respect traditional cultures and rituals, to discover the physical local environment and etc. Nevertheless, tourists visit CBT area with a variety of motives. Understanding tourists’ motivation help in marketing CBT since the tourism providers understand what tourist seek and expects from their vacation. Considering the lack of information regarding motivation research in the Langkawi Islands, this study had been conducted to examine the recreational motives among tourist at Kilim Geopark, Langkawi. This study reveals that main motive of tourist to Kilim Geopark were to enjoy the scenery based on the resources of Langkawi and the beautiful scenery and beaches. Visitors also love to rest and relax during their holiday and to temporary escape from their daily life by spending their leisure time in Langkawi Islands. Hence, it is imperative to conserve Kilim natural environment. This paper demonstrates that understanding tourist motivation for pristine natural resources is a key factor of tourist arrivals which is useful in marketing such area.